Anatomically high division of sciatic nerve and its clinical significance - Kapor, Slobodan; Puškaš, Laslo; Vojvodić, Aleksandar; Mališ, Miloš; Bjelogrlić, Predrag; Cezayirli, Enis; Chisholm, Fraser; Aksić, Milan; Filipović, Branislav (Vojnosanitetski pregled, 2021)
Background / Aim. The sciatic nerve (SN) is a mixed nerve formed in pelvis by joining of L4 - S3 anterior spinal nerve roots. SN can be under the pressure in different regions throughout its course. However, the most frequent site of impingement is under the piriformis muscle which causes the occurrence of piriformis syndrome. High division of SN has its relevance considering the fact that it leads to the compression of nerve resulting in piriformis syndrome. The aim of this study was to determine the connection between anatomical parameters of pelvis and high division of SN, which is considered to be one of the most common causes of piriformis syndrome in both genders. Methods. This study was conducted on 28 formalin fixed cadavers of both genders at the Institute of Anatomy, Faculty of Medicine, University of Belgrade (Belgrade, Serbia) and the Department of Anatomy, School of Medicine, University of St Andrews (St Andrews, United Kingdom). For the measuring of required dimensions, we used a ruler and a caliper. Results. A statistically significant difference in the values of bispinal and bituberal lines was observed. A high division of SN was found on 58.33% of the male cadavers and 80% of the female cadavers. A statistically significant difference in the mean value of the bituberal line between the male and female sex was also recognised. Conclusion. The connection between the anatomical parameters of the pelvis and the level of division of the SN is confirmed. Although on the basis of the results it could be assumed that people with smaller pelvic dimensions would have greater likelihood of developing a piriformis syndrome, the other factors, such as biomechanics related to a wider „Q angle“ in women that could result in a higher incidence of piriformis syndrome, should also be considered.
Keywords: anatomy, regional; cadaver; piriformis muscle syndrome; sciatic nerve; sex characteristics